2017
DOI: 10.4236/jct.2017.84028
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Result of Hyperfractionated High-Dose Proton Beam Radiotherapy for Pediatric Skull Base Chordomas

Abstract: Objective: Proton beam therapy (PBT) may provide good local control for skull base chordoma and reduced toxicities, especially for pediatric patients. Methods: We evaluated the efficacy and safety of hyperfractionated high-dose PBT in6 pediatric patients with newly-diagnosed skull basechordoma who were treated with PBT at our institute from 2011 to 2015. The patients were 5 males and one female, and the median age was 9 years old (range: 5 -13). All patients received surgery before PBT. The median period betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In multivariate analysis, tumor maximum diameter and pathology were significant factors associated with local recurrence. Previous studies have shown that chordoma has more local recurrence than chondrosarcoma [3,13,14]. In a multicenter study of Gamma-knife treatment of 16 Gy (median) for 51 postoperative (n = 30) or recurrent (n = 21, 41%) chondrosarcomas, Kawashima et al achieved good 3-, 5-and 10-year posttreatment local control rates of 87%, 78% and 67%, respectively [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In multivariate analysis, tumor maximum diameter and pathology were significant factors associated with local recurrence. Previous studies have shown that chordoma has more local recurrence than chondrosarcoma [3,13,14]. In a multicenter study of Gamma-knife treatment of 16 Gy (median) for 51 postoperative (n = 30) or recurrent (n = 21, 41%) chondrosarcomas, Kawashima et al achieved good 3-, 5-and 10-year posttreatment local control rates of 87%, 78% and 67%, respectively [33].…”
Section: Discussionmentioning
confidence: 99%
“…Skull base chordoma accounts for 0.5% of primary brain tumors and chondrosarcoma accounts for 0.1% in Japan [1]. The standard treatment for skull base chordoma or chondrosarcoma is tumor resection [2,3]. However, due to the complexity of the anatomy of the base of the skull, it is difficult to completely remove the tumor with a sufficient margin.…”
Section: Introductionmentioning
confidence: 99%
“…Protons and heavy ions, such as carbon ions, can potentially improve dose sparing of normal tissues through the exploitation of the Bragg peak phenomenon, resulting in an increase in energy deposition with penetration depth up to a sharp maximum followed by a rapid decrease at the end of the penetration range ( 3 ). These features permit more precise and conformal dose localization to the target compared with conventional photon RT ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%